2020
DOI: 10.1007/s42729-020-00350-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil P Diffusion and Availability Modified by Controlled-Release P Fertilizers

Abstract: Slow-release fertilizers have been proposed as tools to increase P fertilizer use efficiency in tropical acidic soils with high P adsorption, low P availability, and mobility. However, results have been controversial since soil diversity and the fertilizer itself may influence the results, which is not completely understood. Soil P diffusion and availability were studied in soils with different P fertilization histories, where triple superphosphate (TSP) and single superphosphate (SSP) coated with a polymer or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Expressive P availability was observed in the region where the granules were deposited (5 mm), with a significant reduction in the subsequent areas (25 and 45 mm), regardless of the incubation time. Previous studies have reported similar patterns (Degryse et al., 2013; Lombi et al., 2006; Montalvo et al., 2014; Nunes et al., 2022; Volf & Rosolem, 2021). In addition, the reduced movement of P can be explained by a combination of adsorption reactions between P and soil colloids and its low movement, mainly by diffusion (Novais et al., 2007; Sample et al., 1980; Tiecher et al., 2012).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Expressive P availability was observed in the region where the granules were deposited (5 mm), with a significant reduction in the subsequent areas (25 and 45 mm), regardless of the incubation time. Previous studies have reported similar patterns (Degryse et al., 2013; Lombi et al., 2006; Montalvo et al., 2014; Nunes et al., 2022; Volf & Rosolem, 2021). In addition, the reduced movement of P can be explained by a combination of adsorption reactions between P and soil colloids and its low movement, mainly by diffusion (Novais et al., 2007; Sample et al., 1980; Tiecher et al., 2012).…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have reported similar patterns (Degryse et al, 2013;Lombi et al, 2006;Montalvo et al, 2014;Nunes et al, 2022;Volf & Rosolem, 2021). In addition, the reduced movement of P can be explained by a combination of adsorption reactions between P and soil colloids and its low movement, mainly by diffusion (Novais et al, 2007;Sample et al, 1980;Tiecher et al, 2012).…”
Section: Nutrients Movementmentioning
confidence: 59%
“…High nutrient uptake was observed in the plots treated with both FYM and mineral fertilizers. Ghosh et al [30] suggested that coating P fertilizer granules with layers of organic materials results in higher absorption and efficiency in the use of P compared with uncoated fertilizer [31]. Organic acids released during the decomposition process are good chelating agents for P and increase its availability from applied P fertilizers [32].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of P fertilization in various crops has been studied by several researchers. Volf & Rosolem (2021) studied the use of Triple Super Phosphate (TSP) and Super Phosphate (SP) coated with humic acid to control nutrient release and it was observed that there was no significant increase of P use efficiency on both P-fertilizers. Devi et al (2012) observed the efficiency of P fertilization on soybean by applying different sources of P fertilizer.…”
Section: Introductionmentioning
confidence: 99%